(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Hip fracture-dislocations remain a significant challenge for orthopedic surgeons. The surgical treatment of these fractures is highly complex and demands advanced skills, even for experienced surgeons. The medical applications of virtual reality and 3D printing technology have been expanding due to scientific advancements. The use of 3D-printed models for preoperative planning and the fabrication of anatomically contoured fixation plates has shown promising results. Studies have demonstrated that patients with acetabular fractures combined with hip dislocations treated using preoperatively contoured plates based on 3D-printed models can benefit from reduced surgical time and decreased instrumentation handling during surgery. We present a 3D printing technique designed to facilitate fracture fixation, which has been implemented at Nhan Dan Gia Dinh Hospital, along with a literature review. This technique was applied in the treatment of a hip fracture-dislocation case, following guidelines from existing studies in the medical literature. Case presentation: A 33-year-old male patient with a BMI of 34 kg/m² was admitted to the hospital following a traffic accident, presenting with a posterior hip dislocation accompanied by a posterior column acetabular fracture and a femoral head fracture on the right side. The patient underwent emergency closed reduction of the hip dislocation and skeletal traction. Post-reduction fracture classification was confirmed via computed tomography scan with 3D reconstruction. A preoperative contoured plate was designed based on the 3D model, followed by planned surgical fixation. Three months postoperatively, the patient achieved bone healing and good functional outcomes. Conclusion: The integration of 3D printing technology can provide an effective approach in the treatment of acetabular fractures using precontoured plates, allowing for patient-specific fixation based on complex anatomical characteristics and fracture patterns. This technique enables more accurate anatomic reduction and reduces intraoperative fixation time. With the assistance of 3D printing, it holds great promise as a valuable tool for trauma surgeons in managing severe and complex cases.